Solving the travelling salesman problem by using artificial bee colony algorithm / Siti Hafawati Jamaluddin ... [et al.] - Jamaluddin, Siti Hafawati; Mohd Naziri, Noor Ainul Hayati; Mahmud, Norwaziah; Muhammat Pazil, Nur Syuhada (Universiti Teknologi MARA, Perlis, 2022)
Travelling Salesman Problem (TSP) is a list of cities that must visit all cities that start and end in the same city to find the minimum cost of time or distance. The Artificial Bee Colony (ABC) algorithm was used in this study to resolve the TSP. ABC algorithms is an optimisation technique that simulates the foraging behaviour of honey bees and has been successfully applied to various practical issues. ABC algorithm has three types of bees that are used by bees, onlooker bees, and scout bees. In Bavaria from the Library of Traveling Salesman Problem, the distance from one city to another has been used to find the best solution for the shortest distance. The result shows that the best solution for the shortest distance that travellers have to travel in all the 29 cities in Bavaria is 3974km.